Impact of the severe acute respiratory syndrome coronavirus 2 pandemic on the incidence of type 1 diabetes mellitus in children in Yamanashi, Japan - Tomohiro Saito; Mie Mochizuki; Kisho Kobayashi; Hiromune Narusawa; Daisuke Watanabe; Koichi Makino; Hideaki Yagasaki; Kazumasa Sato; Tomoaki Sano; Masanori Ohta; Hiroshi Yokomichi; Shin Amemiya; et al. (Scientific Reports)
Abstract It has been hypothesized that the biopsychosocial stress associated with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, in combination with the immunological effects of SARS-CoV-2 and pancreatic β-cell dysfunction, may contribute to the onset of type 1 diabetes (T1D) in children. In this study, we documented the incidences of T1D in Yamanashi Prefecture, Japan, from 1986 to 2018, and expanded the analysis to include cases from 2019 to 2022 to evaluate the potential influence of coronavirus disease 2019 (COVID-19) on T1D incidence. The COVID-19 pandemic period was defined as 2020 to 2022. Data spanning from 1986 to 2022 were analyzed in annual increments, while data from 1987 to 2022 were analyzed in 3-year interval increments using Joinpoint regression analysis. Across all analyses, no joinpoints were identified, and a consistent linear increase was observed. These findings suggest that there was no statistically significant change in the incidence of T1D attributable to the COVID-19 pandemic in Yamanashi Prefecture. The annual increase in the incidence was calculated to be 3.384% per year, while the increase in the 3-year interval incidence was calculated to be 2.395% per year. Although the incidence of pediatric T1D among children aged 0–14 years in Yamanashi Prefecture increased during the COVID-19 pandemic (2020–2022), this trend appeared to be a continuation of the pre-2019 increase. The direct or indirect impact of COVID-19 on this trend could not be conclusively determined due to the limited number of cases included in this study.